CuNiSn alloy and preparation method thereof
Through precisely controlled process steps, including smelting, atomization powder making, screening, vacuum degassing and thermal isostatic pressure, the problems of segregation and uneven structure of copper-nickel-tin alloy composition in traditional casting processes are solved, and the performance and quality of the material are significantly improved.
Patent Information
- Application Number
- CN202510040910.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional casting processes are prone to problems such as segregation, uneven structure and difficult processing when preparing copper-nickel-tin alloys, which affect the quality and performance of the material.
Accurately controlled process steps such as smelting, atomization powder making, screening, vacuum degassing and thermal isostatic pressing are adopted to ensure the uniform distribution of CuNiSn alloy components and the optimization of microstructure.
It effectively reduces the composition segregation, pores, cracks and other defects of CuNiSn alloy, improves various performance indicators of the material, and ensures the high quality and reliability of the finished product.
Smart Images

Figure CN119800147A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of alloy preparation, and specifically relates to a CuNiSn alloy and a preparation method thereof. Background Art
[0002] Copper-nickel-tin (CuNiSn) alloy is a high-strength copper-based material with many excellent properties, including high hardness, high elasticity, excellent heat and corrosion resistance, good welding and plating performance, small aging deformation, non-magnetic and environmentally friendly. Due to its excellent mechanical and physical properties, copper-nickel-tin alloy is widely used in many high-tech fields, such as aerospace, consumer electronics, 5G communication infrastructure, engineering machinery and equipment, oil and gas exploration and drilling, and mold manufacturing.
[0003] Traditionally, copper-nickel-tin alloys are prepared by casting. However, this method has some limitations: during the cooling and solidification stages, composition segregation is prone to occur, resulting in an uneven internal structure of the material; the different cooling rates inside and outside the ingot will also cause differences in the distribution of tissues; in addition, the size of the casting is limited by the size of the mold, and the weight of a single ingot is therefore limited. Moreover, due to the relatively low plasticity of the alloy, higher requirements are placed on the subsequent forging process, making it more difficult to achieve the desired shape and size through forging.
[0004] In summary, although copper-nickel-tin alloy has many advantages, the traditional casting process faces challenges in the preparation process, which may affect the quality and performance of the final product. Summary of the invention
[0005] The main purpose of the present application is to provide a CuNiSn alloy and a preparation method thereof, and the present application aims to improve the various properties of the existing CuNiSn alloy.
[0006] To achieve the above objectives, this application provides the following technical solutions:
[0007] A CuNiSn alloy, the components of the CuNiSn alloy and the mass percentage of each component are: Ni: 1wt%-25wt%; Sn: 1w%t-10wt%; Mn: 0.1wt%-2.0wt%; Cu: balance.
[0008] The present application also provides a method for preparing a CuNiSn alloy, the method comprising: smelting a Cu block, a Ni block, and a Sn block to obtain a Cu-Ni-Sn alloy liquid; adding a Mn sheet to the Cu-Ni-Sn alloy liquid for smelting to obtain a Cu-Ni-Sn-Mn alloy liquid, and heating the Cu-Ni-Sn-Mn alloy liquid until the superheat of the Cu-Ni-Sn-Mn alloy liquid reaches a preset temperature; introducing an inert gas to atomize and powder the Cu-Ni-Sn-Mn alloy liquid whose superheat reaches the preset temperature to obtain Cu-Ni-Sn-Mn alloy powder particles; screening the Cu-Ni-Sn-Mn alloy powder particles, and heating and vacuum degassing the screened Cu-Ni-Sn-Mn alloy powder particles; and hot isostatic pressing the vacuum degassed Cu-Ni-Sn-Mn alloy powder particles to obtain a CuNiSn alloy.
[0009] Optionally, the Cu block, the Ni block, and the Sn block are melted in a vacuum environment of 1Pa to 8Pa.
[0010] Optionally, the Cu block, the Ni block and the Sn block are melted by electromagnetic heating.
[0011] Optionally, the electromagnetic heating adopts a gradient heating method.
[0012] Optionally, the superheat degree of the Cu-Ni-Sn-Mn alloy liquid is 150°C to 300°C.
[0013] Optionally, the pressure of the introduced inert gas is 3 MPa to 5 MPa.
[0014] Optionally, the screened Cu—Ni—Sn—Mn alloy powder particles need to be placed in a package for heating and vacuum degassing.
[0015] Optionally, the screened Cu—Ni—Sn—Mn alloy powder particles are heated and vacuum degassed at a temperature of 350° C. to 700° C.
[0016] Optionally, the vacuum degassed Cu—Ni—Sn—Mn alloy powder particles are hot isostatically pressed at a temperature of 800° C. to 1000° C.
[0017] The present application can bring the following beneficial effects: The present application can ensure the uniform distribution of the composition of the CuNiSn alloy and the optimization of the microstructure by precisely controlling the process steps of smelting, atomization powder making, screening, vacuum degassing and hot isostatic pressing. Compared with the traditional casting process, the present application can effectively reduce the composition segregation, pores, cracks and other defects of the CuNiSn alloy, and can improve the various performance indicators of the CuNiSn alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic flow chart of a method for preparing a CuNiSn alloy provided in one embodiment of the present application;
[0019] Figure 2 is a metallographic diagram of a CuNiSn alloy prepared based on the present application provided in another embodiment of the present application;
[0020] Figure 3 This is the metallographic diagram of the existing CuNiSn alloy. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0023] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0024] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0025] In an exemplary embodiment, the present application provides a CuNiSn alloy, wherein the components of the CuNiSn alloy and the mass percentage of each component are: Ni: 1wt% to 25wt%; Sn: 1wt% to 10wt%; Mn: 0.1wt% to 2.0wt%; Cu: balance.
[0026] In this embodiment, nickel (Ni) is one of the key elements to improve the strength and hardness of the copper-based alloy. As the nickel content increases, the hardness and tensile strength of the alloy will be significantly improved. The mass percentage of nickel (Ni) is set to 1wt% to 25wt%, firstly, it can ensure that the CuNiSn alloy has sufficient strength and corrosion resistance, and secondly, it will not cause the alloy cost to be too high under the premise of making the CuNiSn alloy meet the high strength and hardness requirements. Tin (Sn) can significantly improve the elastic modulus of the CuNiSn alloy, giving it better elasticity and recovery ability. The mass percentage of tin (Sn) is set to 1wt% to 10wt%, which can ensure that the CuNiSn alloy achieves the best elastic modulus and wear resistance without excessively enhancing the preparation cost of the alloy. Manganese (Mn) helps to refine the grain structure of the alloy during the smelting process, thereby improving the strength and toughness of the CuNiSn alloy. Setting the mass percentage of manganese (Mn) to 0.1 wt % to 2.0 wt % can enable the CuNiSn alloy to achieve optimal grain refinement and strengthening effects without causing the alloy to become brittle or increasing unnecessary costs.
[0027] In summary, the selection of the above ratios is the optimal range obtained through experimental verification and theoretical analysis on the premise of ensuring that the CuNiSn alloy has the required mechanical properties, physical properties and chemical stability. The CuNiSn alloy with the above ratio can achieve the best balance in strength, hardness, elasticity, corrosion resistance and other aspects.
[0028] Figure 1A method for preparing a CuNiSn alloy according to one embodiment of the present application, such as Figure 1 As shown, the method comprises the following steps:
[0029] S1: 84g of Cu block, 10g of Ni block and 5g of Sn block are sequentially put into a vacuum induction furnace with a vacuum degree of 1Pa, and melted by electromagnetic heating to obtain a Cu-Ni-Sn alloy liquid;
[0030] In this step, the application chooses to use electromagnetic heating instead of other heating methods, mainly considering the unique advantages of electromagnetic heating. For example, electromagnetic heating generates heat by generating eddy current effect inside the metal through the alternating magnetic field. The heat is directly generated from the inside of the material, which can avoid the problems of surface overheating or local temperature unevenness that may occur in traditional heating methods, and help ensure that the temperature distribution of the melt is more uniform throughout the volume, reducing the risk of component segregation. In addition, electromagnetic heating can act directly on the metal itself without the need for conduction through a medium, so the heating speed is faster, which helps to shorten the smelting cycle and improve production efficiency.
[0031] Furthermore, the electromagnetic heating adopts a gradient heating method, which specifically includes the following stages:
[0032] Initial low power heating stage:
[0033] The initial heating power is 40kW, and the heating lasts for 5 minutes. The use of a lower initial heating power is helpful to prevent the vacuum induction furnace from being damaged by sudden high power, and secondly, it can ensure that the gases (such as hydrogen, oxygen, etc.) in the raw materials are gradually released at a relatively low temperature instead of being locked by a sudden increase in temperature, thereby helping to reduce the number of pores in the CuNiSn alloy and improve the density.
[0034] Power gradually increases:
[0035] The heating power was gradually increased from 40kW to 60kW, 80kW, 100kW, and finally to 120kW, and the heating time of each heating power was also maintained at 5 minutes.
[0036] By gradually heating up the temperature, each raw material can adapt to the temperature change evenly, which helps to reduce the risk of thermal stress and deformation caused by rapid heating of the raw materials. In addition, gradual heating up the temperature also helps to better diffuse and mix the raw materials, ensuring that the raw materials are fully contacted and initially fused before melting, laying the foundation for the formation of a uniform alloy liquid.
[0037] High temperature melting stage:
[0038] While maintaining the vacuum degree of the vacuum induction furnace at 1Pa, the heating power is gradually increased from 120kW to between 200kW and 300kW to ensure that all raw materials are completely melted, thereby obtaining a uniformly distributed Cu-Ni-Sn alloy liquid.
[0039] Through observation, when the Cu block begins to melt, it is necessary to introduce an inert gas (such as argon) immediately (for example, within a time window of 5s after the Cu block begins to melt) so that the vacuum induction furnace is adjusted to a slightly positive pressure state (0MPa to 0.01MPa). The introduction of inert gas to establish a slightly positive pressure environment will form a protective gas barrier on the top of the furnace. This barrier helps to maintain the stability of the melt surface and can reduce fluctuations caused by temperature fluctuations or electromagnetic forces, thereby effectively inhibiting the metal vapor and fine droplets generated by each raw material during the melting process from diffusing outward, thereby reducing the possibility of droplets splashing onto the furnace wall or other parts. In addition, by introducing inert gas and creating a slightly positive pressure environment in the furnace, oxygen can be effectively excluded, ensuring that the inside of the furnace is an environment that is almost oxygen-free. Under such conditions, the alloy components will not come into contact with oxygen, thereby avoiding the formation of oxide inclusions.
[0040] It should be noted that when the Cu block begins to melt, the surface of the copper will gradually be exposed to any residual oxygen in the furnace environment. Even under high vacuum conditions, it is difficult to completely exclude all oxygen. Therefore, if the inert gas cannot be introduced in a very short time to create a slightly positive pressure environment, the molten copper liquid is likely to react with the residual oxygen to form copper oxide inclusions. These oxides will not only affect the purity and uniformity of the alloy, but may also cause the mechanical properties of the finished material to deteriorate. In addition, if the inert gas barrier is not established quickly after the copper begins to melt, these metal vapors and droplets may diffuse outward due to electromagnetic forces or temperature fluctuations, causing unnecessary splashing, which not only causes waste of raw materials, but may also contaminate the interior of the furnace and other equipment components, increasing cleaning costs and maintenance difficulties.
[0041] In summary, through gradient heating, the temperature in the furnace can be gradually increased so that each raw material can adapt to the temperature change evenly. This can avoid the problem of local overheating or uneven temperature caused by rapid heating in certain areas, and ensure that the temperature distribution of the entire melt is more uniform. If the temperature rises directly from low temperature to high temperature, each metal material may produce thermal stress due to the sudden temperature change, resulting in cracks or other forms of damage. The use of gradient heating can effectively reduce this thermal shock, allowing each material to gradually adapt to the temperature change, thereby reducing the risk of deformation and cracking. More importantly, for metals with different melting points (such as Cu, Ni, Sn), gradient heating can better control their melting order, ensuring that the low-melting-point metal will not melt completely too early, but will melt synchronously with the high-melting-point metal and be fully mixed, thereby obtaining a uniform alloy liquid.
[0042] S2: Add 1 g of Mn sheet into the Cu-Ni-Sn alloy liquid for melting, and obtain Cu-Ni-Sn-Mn alloy liquid after melting. At this time, continue to heat the Cu-Ni-Sn-Mn alloy liquid until the superheat of the Cu-Ni-Sn-Mn alloy liquid reaches 150°C.
[0043] S3: introducing an inert gas at a pressure of 3 MPa to atomize and powder the Cu-Ni-Sn-Mn alloy liquid having a superheat of 150° C. to obtain Cu-Ni-Sn-Mn alloy powder particles;
[0044] In this step, the present application adopts the following atomization powder making process:
[0045] Preheat the inert gas: Before the inert gas enters the nozzle, it is preheated to a temperature close to but slightly below the melting point of the alloy (for example, for Cu-Ni-Sn-Mn alloy, it can be preheated to below about 1085°C), which helps maintain the fluidity of the molten metal and reduces the stress caused by excessive temperature difference.
[0046] Pulse gas injection: Pulse gas injection means that the pressure of gas injection is switched quickly at a certain frequency (such as hundreds of times per second). For example, in each pulse cycle, 3MPa is first injected at a high pressure for a period of time (such as a few milliseconds), then the pressure is quickly reduced to a lower pressure (such as 1MPa), and then restored to a high pressure state. This pulse injection method with rapid switching of injection pressure can generate a strong shock wave at each high pressure moment, which can effectively break up the newly formed large-sized droplets, thereby obtaining finer and more evenly distributed powder particles. At the same time, the low pressure period is conducive to the rapid dissipation of heat, further accelerating the solidification process of the powder.
[0047] Rotating magnetic field assistance: Since the Cu-Ni-Sn-Mn alloy contains a certain proportion of conductive elements (such as copper and nickel), a rotating magnetic field can be applied around the nozzle. The rotating magnetic field can induce an eddy current effect inside the molten metal, so that the droplets are subjected to additional centrifugal force during the ejection process. This not only helps to further refine the powder particles, but also improves the regularity of their shape and reduces the proportion of irregular particles. Specifically, an electromagnetic coil can be used to surround the nozzle, and an alternating current can be provided by an external power supply to generate the required rotating magnetic field. The magnetic field strength can be adjusted according to actual needs to achieve the best effect.
[0048] Multi-stage cooling and graded collection: The cooling zone is divided into several stages, each stage is equipped with different types of cooling media (such as air, water mist, etc.), and targeted cooling is implemented according to the flight trajectory of the powder particles. For example, a milder cooling method is used near the nozzle, while a more intense cooling method is used at a location far from the nozzle.
[0049] By implementing the above-mentioned atomization powder making process, the present application can effectively improve the uniformity, purity and shape regularity of the Cu-Ni-Sn-Mn alloy powder particles, significantly reduce component segregation and internal defects, and optimize the fluidity and particle size distribution of the powder. It can not only ensure that the Cu-Ni-Sn-Mn alloy has a highly consistent microstructure and excellent mechanical properties, but also enhance its density and strength.
[0050] S4: screening the Cu-Ni-Sn-Mn alloy powder particles, placing the screened Cu-Ni-Sn-Mn alloy powder particles into a bag, and heating and vacuum degassing at a temperature of 350° C.;
[0051] In this step, the purpose of screening the Cu-Ni-Sn-Mn alloy powder particles is to remove oversized or undersized particles (oversized particles will cause pores or inclusions, while undersized particles will generate too much dust during the pressing process, affecting the molding quality. By screening and removing these inappropriate particles, the probability of defects such as pores and cracks in the finished product can be effectively reduced, and the overall quality of the alloy can be improved) to ensure that the Cu-Ni-Sn-Mn alloy powder particles loaded into the package are uniform. The uniform Cu-Ni-Sn-Mn alloy powder particles help to form a more uniform microstructure. During the hot isostatic pressing process, the contact and bonding between the powder particles will be more regular, thereby reducing local density differences and improving the uniformity and density of the Cu-Ni-Sn-Mn alloy as a whole.
[0052] In addition, the sheath is made of a high temperature and high pressure resistant material (such as stainless steel, titanium alloy, etc.) to ensure that it can withstand the high temperature and high pressure environment in the hot isostatic pressing process.
[0053] S5: The vacuum degassed Cu-Ni-Sn-Mn alloy powder particles are loaded into a hot isostatic pressing device for hot isostatic pressing to obtain a CuNiSn alloy, wherein the temperature of the hot isostatic pressing device is set to 800°C, the pressure is set to 100 MPa, and the heat preservation and pressure holding time is set to 2 hours.
[0054] In another exemplary embodiment, the present application also provides a method for preparing a CuNiSn alloy, comprising the following steps:
[0055] S10: 70.5 g of Cu block, 20 g of Ni block, and 8 g of Sn block are sequentially put into a vacuum induction furnace with a vacuum degree of 5 Pa, and smelted by electromagnetic heating to obtain a Cu-Ni-Sn alloy liquid;
[0056] In this step, the heating method of gradient heating is also adopted, which will not be described here. However, unlike the above-mentioned embodiment, this embodiment further adopts a liquid sealing method to control the splashing of liquid droplets and prevent the oxidation of molten metal. Specifically, the specific implementation steps of the liquid sealing method are as follows:
[0057] Before smelting the above raw materials, the sealant is first heated to above its melting point to make it a fluid sealing liquid, and the sealing liquid is poured into the top of the furnace to ensure that it can be evenly distributed in the upper area inside the furnace; then, the metal raw materials to be melted are added according to the smelting procedure described in the previous embodiment, and the heating process is started. As the temperature rises, the metal raw materials gradually melt, while the sealing liquid is always maintained above them, thereby isolating the air and preventing splashing.
[0058] It should be noted that for the smelting of CuNiSn alloy, considering that its melting point is about 1085°C, this embodiment uses molten salt as a sealant, and preferably uses a eutectic salt of potassium chloride (KCl) and sodium chloride (NaCl). The eutectic mixture of potassium chloride (KCl) and sodium chloride (NaCl) has a low melting point of about 770°C, which is much lower than the melting point of CuNiSn alloy. Therefore, during the smelting process, the eutectic salt of potassium chloride (KCl) and sodium chloride (NaCl) will always remain in a liquid state and will not solidify into a solid state, so that it can continue to effectively cover the surface of the molten metal and provide a stable barrier. In addition, potassium chloride (KCl) and sodium chloride (NaCl) show good chemical inertness to most metals including copper, nickel, tin, etc., and are not easy to react with these metals at high temperatures, which ensures that they will not introduce unnecessary impurities and will not change the alloy composition. Further, the molten salt is cooled and solidified after smelting, and can be separated from the alloy ingot by simple physical methods (such as screening or pouring). Furthermore, these salts can be processed and reused, reducing waste and lowering long-term operating costs.
[0059] S20: adding 1.5 g of Mn flakes into the Cu-Ni-Sn alloy liquid and continuing to smelt, to obtain a Cu-Ni-Sn-Mn alloy liquid after smelting. At this time, continue to heat the Cu-Ni-Sn-Mn alloy liquid until the superheat of the Cu-Ni-Sn-Mn alloy liquid reaches 200°C.
[0060] S30: introducing an inert gas at a pressure of 4 MPa to atomize and powder the Cu-Ni-Sn-Mn alloy liquid having a superheat of 200° C. to obtain Cu-Ni-Sn-Mn alloy powder particles;
[0061] S40: screening the Cu-Ni-Sn-Mn alloy powder particles, placing the screened Cu-Ni-Sn-Mn alloy powder particles into a bag, and heating and vacuum degassing at a temperature of 500° C.;
[0062] S50: The vacuum degassed Cu-Ni-Sn-Mn alloy powder particles are loaded into a hot isostatic pressing device for hot isostatic pressing to obtain a CuNiSn alloy, wherein the temperature of the hot isostatic pressing device is set to 900° C., the pressure is set to 120 MPa, and the heat preservation and pressure holding time is set to 4 hours.
[0063] In another exemplary embodiment, the present application also provides a method for preparing a CuNiSn alloy, comprising the following steps:
[0064] S100: 77.5 g of Cu block, 15 g of Ni block, and 7 g of Sn block are sequentially put into a vacuum induction furnace with a vacuum degree of 8 Pa, and smelted by electromagnetic heating to obtain a Cu-Ni-Sn alloy liquid;
[0065] In this step, a gradient heating method is also used, which will not be described in detail here.
[0066] S200: adding 0.5 g of Mn flakes into the Cu-Ni-Sn alloy liquid and continuing to smelt, to obtain a Cu-Ni-Sn-Mn alloy liquid after smelting. At this time, continue to heat the Cu-Ni-Sn-Mn alloy liquid until the superheat of the Cu-Ni-Sn-Mn alloy liquid reaches 300°C.
[0067] S300: introducing an inert gas with a pressure of 5 MPa to atomize and powder the Cu-Ni-Sn-Mn alloy liquid with a superheat of 300° C. to obtain Cu-Ni-Sn-Mn alloy powder particles;
[0068] S400: screening the Cu-Ni-Sn-Mn alloy powder particles, placing the screened Cu-Ni-Sn-Mn alloy powder particles into a bag, and heating and vacuum degassing at a temperature of 700° C.;
[0069] S500: The vacuum degassed Cu-Ni-Sn-Mn alloy powder particles are loaded into a hot isostatic pressing device for hot isostatic pressing to obtain a CuNiSn alloy, wherein the temperature of the hot isostatic pressing device is set to 1000° C., the pressure is set to 140 MPa, and the heat preservation and pressure holding time is set to 5 hours.
[0070] In the above embodiments, the reason why the Cu-Ni-Sn-Mn alloy liquid needs to be heated to an overheated state after it is obtained is that: when the Cu-Ni-Sn-Mn alloy liquid reaches an overheated state, its viscosity will decrease, and its fluidity will be significantly improved, which can ensure that the Cu-Ni-Sn-Mn alloy can fully fill the mold and reduce defects (such as pores and shrinkage). In addition, overheating can accelerate the diffusion rate between the components in the Cu-Ni-Sn-Mn alloy, so that the component segregation phenomenon that may exist can be alleviated or eliminated, which helps the Cu-Ni-Sn-Mn alloy to form a more uniform microstructure. Furthermore, overheating helps to reduce the viscosity of the Cu-Ni-Sn-Mn alloy liquid, so that the non-metallic inclusions therein are more easily floated to the surface and removed, thereby improving the purity of the Cu-Ni-Sn-Mn alloy. It should be noted that in the above embodiments, the superheat temperature is limited to between 100°C and 300°C based on the following considerations: if the superheat is lower than 100°C, the viscosity of the Cu-Ni-Sn-Mn alloy liquid may still be high, which will affect its fluidity and filling capacity. And a lower superheat means that the diffusion rate between elements is slower, which may cause component segregation inside the alloy, affecting the microstructure and performance consistency of the final product. On the contrary, if the superheat is greater than 300°C, the evaporation loss of certain alloying elements (especially relatively volatile elements such as tin (Sn) and manganese (Mn)) will be accelerated, causing the alloy composition to deviate from the designed ratio, thereby affecting the alloy performance. For example, the boiling point of tin (Sn) is about 2602°C, but as the temperature increases, its vapor pressure will also increase, which may cause significant volatilization losses in extreme cases. In addition, too high a temperature will make the Cu-Ni-Sn-Mn alloy liquid too active, increase the risk of droplet splashing, and may also destroy the uniform distribution that has been formed, which is not conducive to the quality control of subsequent processing steps. Therefore, the superheat temperature is limited to between 100°C and 300°C in order to ensure that the Cu-Ni-Sn alloy liquid has sufficient fluidity to achieve a good forming effect, and at the same time can effectively avoid problems such as composition changes, oxidation risks, and equipment damage caused by excessively high temperatures. Further, after experiments, this application uses 200°C as the optimal superheat. This temperature is a compromise solution that takes into account both composition stability and equipment safety while ensuring that the Cu-Ni-Sn-Mn alloy liquid has sufficient fluidity to achieve a good forming effect. This temperature can not only promote composition homogenization and reduce defects, but also control volatilization losses and oxidation risks to a certain extent. It is a reasonable choice after comprehensive consideration of multiple factors.
[0071] In the above embodiments, the vacuum degree of the vacuum induction furnace is set to 1Pa to 8Pa because within this vacuum degree range, it can maintain good heat conduction efficiency to facilitate the melting process, and will not cause excessive heat loss due to excessive vacuum, affecting the melting speed and energy consumption. For the present application, if the vacuum degree is higher than 8Pa, it means that the gas pressure in the environment is relatively high, and more gas molecules may be mixed into the melt, which will increase the risk of inclusions and pore formation, thereby reducing the purity and mechanical properties of the CuNiSn alloy. In addition, under higher air pressure, the molten metal is more likely to be exposed to residual oxygen or other reactive gases, causing unnecessary oxidation problems. On the contrary, if the vacuum degree is lower than 1Pa, some alloying elements may be lost due to excessive evaporation, especially for alloys containing low-boiling point elements, which will change the chemical composition of the alloy, thereby affecting its predetermined physical and mechanical properties. In summary, in this application, setting the vacuum degree of the vacuum induction furnace to 1Pa to 8Pa is the optimal choice that comprehensively considers the stability of the CuNiSn alloy composition, the smelting quality, and the feasibility of operation. Deviating from this range may have an adverse effect on the quality of the final product and the production process. Further, after experiments, this application uses 5Pa as the optimal vacuum degree, which can maintain good heat conduction efficiency to facilitate the melting process, but will not cause excessive heat loss due to excessive vacuum, affecting the smelting speed and energy consumption, which helps to improve the smelting efficiency while reducing energy costs.
[0072] In the above embodiments, the pressure of the inert gas introduced is set to 3Mpa to 5Mpa. Within this pressure range, the inert gas can generate enough impact force to break up the primary large-sized droplets, thereby obtaining finer and evenly distributed powder particles. If the pressure is too high (greater than 5Mpa), the powder particles will be too fine, thereby increasing the risk of dust explosion and easily causing losses during subsequent processing. If the pressure is too low (less than 3Mpa), the impact force generated by the gas is not enough to effectively break up larger droplets, resulting in the presence of larger particles in the final powder, thereby affecting the quality of the alloy.
[0073] In the above embodiments, the present application performs vacuum degassing on Cu-Ni-Sn-Mn alloy powder particles under a temperature environment of 350°C to 700°C. Within this temperature range, on the one hand, the gases (such as hydrogen, oxygen, etc.) adsorbed on the powder surface or in tiny pores can be effectively desorbed and escaped, thereby reducing the possibility of these gases forming pores or other defects during subsequent processing. On the other hand, the temperature range is high enough to activate the gas molecules to detach from the surface of the powder particles, but not enough to cause significant diffusion or phase change between the alloy elements, thereby ensuring the stability of the alloy composition. If it is greater than 700°C, it will lead to increased diffusion between the elements inside the alloy, and even induce phase change, thereby changing the microstructure of the alloy and affecting the mechanical properties and other characteristics of the alloy. On the contrary, if it is less than 350°C, it will not provide enough energy to activate the desorption process of the adsorbed gas molecules, resulting in incomplete degassing, and the residual gas may form defects in subsequent processing. Therefore, the temperature range of 350°C to 700°C is the best choice based on the physical and chemical properties of the Cu-Ni-Sn-Mn alloy powder particles, the degassing requirements and the actual production conditions. This temperature range can not only ensure effective degassing treatment, but also avoid the adverse effects caused by too high or too low temperature, providing a reliable guarantee for the preparation of high-quality alloy products. Further, after experiments, this application uses 500°C as the optimal degassing temperature. On the one hand, vacuum degassing at this temperature can most effectively prevent the metal from contacting oxygen in the air in an inert atmosphere or vacuum, thereby avoiding the occurrence of oxidation; on the other hand, the temperature is high enough to activate the desorption process of gas molecules, but not enough to cause significant diffusion or phase change between the elements inside the alloy, which helps to maintain the microstructure of the CuNiSn alloy stable without affecting its mechanical properties and other characteristics.
[0074] Figure 2 This is a metallographic diagram of a CuNiSn alloy prepared by the method described in this application; Figure 3 This is the metallographic diagram of the existing CuNiSn alloy. Figure 2 It can be seen that the CuNiSn alloy shows a finer and more uniform grain structure. This is due to the pulsed gas injection and rotating magnetic field auxiliary technology used in the atomization powder making process, which helps to refine the powder particles and form a finer microstructure in the subsequent hot isostatic pressing process. In addition, it can be seen that Figure 2 In the embodiment, the CuNiSn alloy has fewer pores, cracks and other types of defects, indicating that the good degassing treatment and optimized smelting conditions provided by the present application ensure the purity of the alloy interior and reduce the presence of non-metallic inclusions. Figure 3 It can be seen that the existing CuNiSn alloy exhibits larger grains and irregular grain boundaries, which is one of the problems that are prone to occur in traditional casting processes, resulting in an uneven internal structure of the material. In addition, Figure 3 The existing CuNiSn alloy has more pores and shrinkage, and these defects will affect the overall performance and reliability of the alloy.
[0075] In summary, by comparison Figure 2 and Figure 3 It can be seen that the preparation method proposed in this application can significantly improve the microstructure and uniformity of the composition distribution of the CuNiSn alloy, reduce the number and severity of defects, and thus improve the overall quality of the final product. This improvement is crucial to improving the application performance of CuNiSn alloy in high-tech fields, such as aerospace, consumer electronics, 5G communication infrastructure, etc., and can provide more reliable and high-performance material solutions.
[0076] Furthermore, the present application conducted a performance comparison between the CuNiSn alloy prepared by the present method and the existing CuNiSn alloy through experiments. The specific comparison results are shown in Table 1:
[0077] Table 1
[0078]
[0079]
[0080] As can be seen from Table 1, the CuNiSn alloy prepared by the method of the present application is superior to the existing CuNiSn alloy in multiple performance indicators. These improvements not only improve the basic mechanical properties of the CuNiSn alloy, but also enhance its corrosion resistance and thermal stability, making it more suitable for application fields with high performance requirements such as aerospace, electronic products, and the automotive industry.
[0081] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A CuNiSn alloy, characterized in that: The components of the CuNiSn alloy and the mass percentage of each component are: Ni: 1wt% to 25wt%; Sn: 1wt%~10wt%; Mn: 0.1 wt% to 2.0 wt%; Cu: remainder.
2. A method for preparing a CuNiSn alloy, characterized in that: The method comprises: The Cu block, the Ni block and the Sn block are melted to obtain a Cu-Ni-Sn alloy liquid; adding Mn flakes into the Cu-Ni-Sn alloy liquid for melting to obtain a Cu-Ni-Sn-Mn alloy liquid, and heating the Cu-Ni-Sn-Mn alloy liquid until the superheat of the Cu-Ni-Sn-Mn alloy liquid reaches a preset temperature; Passing inert gas to atomize and powder the Cu-Ni-Sn-Mn alloy liquid whose superheat reaches a preset temperature, so as to obtain Cu-Ni-Sn-Mn alloy powder particles; Screening the Cu-Ni-Sn-Mn alloy powder particles, and heating and vacuum degassing the screened Cu-Ni-Sn-Mn alloy powder particles; The Cu—Ni—Sn—Mn alloy powder particles after vacuum degassing are hot isostatically pressed to obtain a CuNiSn alloy.
3. The method for preparing a CuNiSn alloy according to claim 2, characterized in that: The Cu block, the Ni block, and the Sn block are melted in a vacuum environment of 1 Pa to 8 Pa.
4. The method for preparing a CuNiSn alloy according to claim 2, characterized in that: The Cu block, the Ni block and the Sn block are melted by electromagnetic heating.
5. The method for preparing a CuNiSn alloy according to claim 4, characterized in that: The electromagnetic heating adopts a gradient heating method.
6. The method for preparing a CuNiSn alloy according to claim 2, characterized in that: The superheat degree of the Cu-Ni-Sn-Mn alloy liquid is 150°C to 300°C.
7. The method for preparing a CuNiSn alloy according to claim 2, characterized in that: The pressure of the inert gas introduced is 3Mpa to 5Mpa.
8. The method for preparing a CuNiSn alloy according to claim 2, characterized in that: The screened Cu-Ni-Sn-Mn alloy powder particles need to be placed in a package for heating and vacuum degassing.
9. The method for preparing a CuNiSn alloy according to claim 2, characterized in that: The screened Cu—Ni—Sn—Mn alloy powder particles are heated and vacuum degassed at a temperature of 350° C. to 700° C.
10. The method for preparing a CuNiSn alloy according to claim 2, characterized in that: The vacuum degassed Cu—Ni—Sn—Mn alloy powder particles are hot isostatically pressed at a temperature of 800° C. to 1000° C.